The hollowing of American public administration - Durant, Robert F.; Rosenbloom, David H. (2017)
Effectively linking public administration theory to practical relevance has proven a difficult task. We argue, however, that the theory?practice conundrum is but a symptom of a more fundamental problem in public administration: the hollowing out of the field. Despite research advances, hollowing occurs because of the field?s conceptually muddled and decontextualized normative pillars, problematic macrodynamic foundations, and imbalanced scaffolding for integrating its multiple research narratives and methodologies efficaciously for both scholars and practitioners. To illustrate our points, we first critique the logic and empirical basis of two major pillars of public administration: efficiency and social equity. We then show how and why the field also has problematic macrodynamic foundations due to its failure to incorporate important developments in cognate fields related to administrative history, contexts, and processes. We next offer a problem-centered organizational framework for the field to help address the scaffolding problem in public administration. - Reproduced.
Keywords: Administrative efficiency; Public administration - research; Public administration